Military aid as complicity in international crimes - Drolec Sladojević, Tina (Pravnik, 2015)
Provision of military aid in contemporary armed conflicts, which involve commission of international crimes may, under certain circumstances, be characterized as complicity in those crimes. Political decisions of states to provide military aid to another state or to a non-state actor in situations involving the commission of international crimes should be qualified as acts of state and should, accordingly, be addressed within the framework of international law of state responsibility. Additionally, these decision should invoke individual criminal responsibility within the realm of international criminal law. The article exposes the apparent tension between the existing rules relating to the provision of military aid as they derive from international criminal law, on the one hand, and the law of state responsibility, on the other. In contemporary international law practice, the focus is on the individual criminal responsibility of (an) individual (military or political) leader(s) while the responsibility of a state remains unclear. This tension is addressed particularly in the light of the recent developments in international criminal law. Observing that the articulation of relationship between state and individual responsibility in the realm of international crimes remains for the most part unclear, the provision of military aid should necessarily entail the implementation of a state policy, and should, therefore, be considered as an act of state in addition to an act of an individual.
Keywords: kazniva dejanja; mednarodno vojaško sodelovanje; odgovornost